Uporaba vprašalnika za oceno kakovosti življenja pri otrocih s cerebralno paralizo - Volčini, Lara (Rehabilitacija (Ljubljana), 2021)
Background: Impaired gross motor function and other problems of a child with cerebral palsy (CP) can influence his/her quality of life. Only one broader study on the possible impact of CP on health related quality of life (HRQoL) has been run in Slovenia. We wanted to analyse what impact cerebral palsy has on a child%s quality of life. We wanted to find a simple, free-of-charge HRQoL test for children with CP and check its clinical use in a small group of children. We also wanted to find if HRQoL evaluation scores differ among children and their parents. Methods: After the translation of the Cerebral Palsy Quality of Life-Child questionnaire (CP QOL-Child) into Slovene language, we invited children and their parents who were referred to the rehabilitation program at the University Rehabilitation Institute of the Republic Slovenia. They filled in the CP QOL-Child self-report version for children or primary caregiver version. Results: We included 10 children (aged from nine to 12 years) and their parents. Children and their parents rated their quality of life as good. A fair share of parents rated the quality of life lower in comparison with their children, especially parents of children with lower gross motor function. Children with higher gross motor function scored their HRQoL higher in comparison to children with lover gross motor function. Conclusion: Slovenian translation of the CP QOL-Child questionnaire is useful in clinical practice. Before its further use, psychometric properties should be assessed in a larger number of children with cerebral palsy.
Keywords: Cerebral Palsy; cerebralna paraliza; Child; družina; family; kakovost življenja; otrok; quality of life; questionnaire; rehabilitation; vprašalnik